1998
DOI: 10.1111/j.1398-9995.1998.tb03977.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat treatment modifies the allergenicity of beef and bovine serum albumin

Abstract: The effect of heat on the allergenicity of beef and bovine serum albumin was investigated among 10 toddlers skin prick test (SPT)‐positive to raw and cooked beef. The meat‐allergy diagnosis was confirmed during double‐blind, placebo‐controlled food challenge (DBPCFC) with 180 g of beef cooked for 5 min at 100°C. SPT with homogenized and freeze‐dried beef, and heated and unheated bovine serum albumin were performed. Both heated and unheated bovine serum albumin, homogenized beef, and freeze‐dried beef were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 14 publications
1
33
0
2
Order By: Relevance
“…3 Many observations in humans have called attention to the possible sensitizing property of this kind of vaccine. With the increasing number of reports about the diseases caused by BSA, [4][5][6][7] the problem of residual bovine serum proteins, especially BSA, in viral vaccines has drawn more and more attention. 8 Many methods were tested to replace or decrease the concentration Recently, the upper limit for the content of BSA was precisely established in the Pharmacopeia of China.…”
Section: Introductionmentioning
confidence: 99%
“…3 Many observations in humans have called attention to the possible sensitizing property of this kind of vaccine. With the increasing number of reports about the diseases caused by BSA, [4][5][6][7] the problem of residual bovine serum proteins, especially BSA, in viral vaccines has drawn more and more attention. 8 Many methods were tested to replace or decrease the concentration Recently, the upper limit for the content of BSA was precisely established in the Pharmacopeia of China.…”
Section: Introductionmentioning
confidence: 99%
“…13) Werfel et al 14) have reported that the allergenicity of BSA and BGG could be reduced by sufficient heating. On the other hand, Fiocchi et al 15) have reported that, in some cases, heated BSA caused an allergic reaction. There have also been reports that beef allergy showed high cross-reactivity with other meat allergies.…”
mentioning
confidence: 99%
“…Bovine serum albumin (BSA) (Bos d 6), which is a heat-labile protein, is a major allergen in beef but a minor allergen in milk [81][82][83][84]. Accordingly, beef allergic individuals are at risk of being allergic to cow's milk and vice versa.…”
Section: Minor Allergensmentioning
confidence: 99%